3-Degree of Freedom Gap Clearance Control of A New Generation Maglev Conveyance Vehicle - Kadir ERKAN (Gazi Üniversitesi Fen Bilimleri Dergisi, 2018)
In this study, a transport vehicle based on magnetic levitation technology, which is obtained by combining 3 linear motors and hybrid electromagnets, has been proposed for providing a flexible and modular conveyance system. The magnetic suspension forces have been obtained using 3-dimensional finite element analysis. The proposed system has nonlinear dynamics and shows unstable system characteristics from the point view of control engineering, even for the linearized form. Linear system models corresponding to the 3-axis motion dynamics have been developed to implement controller designs that will stabilize the system. Using the linear models developed for each motion axis, the controllers providing stability and at the same time tracking capability the given reference have been designed considering the topology of I-PD controller. When the I-PD controller is compared with the conventional PID controller; it removes the zero close to origin and eliminates the excessive overshoot that threatens the stability. In controller designs, the use of the coefficient diagram method with the canonical polynomial approach, which provides considerably easier design and adaptation than the counterparts, has been proposed. The magnetic levitation control in the 3-degree of freedom was experimentally performed on the test setup, and the effectiveness of the proposed control approach was successfully demonstrated and verified.